2020
DOI: 10.3892/ol.2020.11801
|View full text |Cite
|
Sign up to set email alerts
|

Patients with advanced non‑small cell lung cancer with EGFR mutations in addition to complex mutations treated with osimertinib have a poor clinical outcome: A real‑world data analysis

Abstract: The present study aimed to investigate the clinical characteristics and outcomes of patients with advanced non-small cell lung cancer (NSCLC) treated with osimertinib, and focused on the resistance mechanism to osimertinib in a real-world setting. Data from 128 patients with advanced NSCLC who were treated with osimertinib between March 2015 and November 2018 at the Chinese People's Liberation Army General Hospital (Beijing, China) were retrospectively collected, and the associations between mutation types and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…SMARCA2 and SMARCA4 gene products were both retained, and this phenotype could have contributed to chemotherapy failure and immune system anergy, 30 also exemplified by scantness of tumor-infiltrating lymphocytes, PD-L1 negativity, ineffectiveness of pembrolizumab (case number 2), or mutanome-derived low neoantigens of the EGFR-altered case number 1. 31 , 32 Furthermore, resistance to EGFR tyrosine kinase inhibitor could have derived from alternative signaling coactivation through IGFR1 , 33 MYC , 34 CCND1 , 35 or CDK2 CNVs, also conferring worse prognosis through TP53 inactivation. 34 , 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMARCA2 and SMARCA4 gene products were both retained, and this phenotype could have contributed to chemotherapy failure and immune system anergy, 30 also exemplified by scantness of tumor-infiltrating lymphocytes, PD-L1 negativity, ineffectiveness of pembrolizumab (case number 2), or mutanome-derived low neoantigens of the EGFR-altered case number 1. 31 , 32 Furthermore, resistance to EGFR tyrosine kinase inhibitor could have derived from alternative signaling coactivation through IGFR1 , 33 MYC , 34 CCND1 , 35 or CDK2 CNVs, also conferring worse prognosis through TP53 inactivation. 34 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…31 , 32 Furthermore, resistance to EGFR tyrosine kinase inhibitor could have derived from alternative signaling coactivation through IGFR1 , 33 MYC , 34 CCND1 , 35 or CDK2 CNVs, also conferring worse prognosis through TP53 inactivation. 34 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that the factors that were non-significant in our multivariate analysis but tended to be prognostic factors in univariate analysis were consistent with those previously reported. Interestingly, Chang et al recently reported that osimertinib efficacy was diminished in a group of patients who had a complex mutation apart from the T790M mutation 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Ortiz et al described a patient who acquired a KRAS G12S mutation with the administration of Osimertinib. Cellular investigation showed that, compared to KRAS wild type transduced cells (PC9 KRAS-wt ), G12S mutation cells (PC9 KRAS G12S ) appeared less sensitive to Osimertinib (9), suggesting that KRAS mutations underlie the resistance to Osimertinib (10)(11)(12). Although KRAS and EGFR mutations are thought to exist in a mutually exclusive manner (13), with the introduction of high-sensitivity large-scale mutation analysis, multiple studies have unveiled the co-existence of EGFR mutations and other dominant mutations such as those of KRAS (14).…”
Section: Discussionmentioning
confidence: 99%